Persepsi Mahasiswa terhadap Simulasi Pelatihan Resusitasi Jantung Paru dengan Media Virtual Reality di Fakultas Kedokteran Universitas Wahid Hasyim, Semarang, Indonesia: Penelitian - Wulandari, Nur Arfa; Herlambang, Penggalih Mahardika; Rido Muid, Rido Muid; Annanto, Gilar Pandu; Firmansyah, Erik; Prasetyo, Sandif (Cermin Dunia Kedokteran, 2026)
Background: Cardiac arrest is a medical emergency requiring immediate action to prevent sudden death. Virtual Reality (VR) technology has been introduced to enhance the effectiveness of cardiopulmonary resuscitation (CPR) training. This study aims to evaluate students’ perceptions of using VR in CPR training simulations at the Faculty of Medicine, Wahid Hasyim University, Semarang. Methods: This study used a cross-sectional design with a descriptive quantitative approach. A total of 30 first-semester students were selected using a purposive sampling technique. Data were collected using a Likert-scale questionnaire based on the Technology Acceptance Model (TAM) that included Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Attitude Toward Using (ATU), and Behavioral Intention to Use (BIU), as well as variables of simulation effectiveness and VR technical difficulty. Data were analyzed descriptively. Results: The average PU score of 4.15 and PEOU score of 4.20 reflect positive perceptions of the added value and ease of use of VR. ATU scored 4.39, and BIU scored 4.08, indicating positive attitudes and strong intentions to continue using VR in CPR training. However, some students reported technical challenges, with an average score of 2.67. Conclusion: Students demonstrated positive perceptions of using VR in CPR training simulations, with high scores across all TAM aspects.